(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
The Mini Ilizarov is an external fixator that is useful for treating various hand injuries. Its modern development began in the 1990s at the Ilizarov Institute in Russia and has several benefits. It is used for fracture management and can also be used for releasing joint contractures, bone lengthening, and correcting congenital malformations. It is favored for its ease of use, small size, and strong holding power. The device can be customized for different types of fractures, deformities, and soft tissue damage, and can be used on multiple bones simultaneously, reducing the number of interventions and treatment time. Despite its popularity globally and among hand surgeons, it is not widely used in Pakistan. This review aims to encourage young surgeons to use this technique and to inspire further clinical applications in the future.